Eco-Play: Menanam Pohon dan Menghias Botol Bekas untuk Mengasah Kreativitas serta Kepedulian Lingkungan pada Anak Usia Dini - Giwang Sekar Windayu; Pelean Alexander Jonas Sitompul; Tukiman Tukiman; Saila Faradina Aidi; Nabila Kusari Yanti; Kezia Jeditha Krisnanto; Marchelo Boas Permata; Rika Wahyu Permata; Al Firdaus Nawawi; Nafhatul Unsi; Sofiyyah Wardah Widad (JURNAL PENGABDIAN MASYARAKAT AKADEMISI, 2024)
Eco-Play is a creative learning activity designed for elementary school students to introduce the concept of environmental sustainability through the activity of coloring and recycling plastic bottles into plant pots. In this program, children are encouraged to explore their creativity by decorating used plastic bottles using paint and various eco-friendly materials. After coloring, the decorated plastic bottles are used as pots to plant small plants, such as flowers or vegetables, which can later be cared for by the children at home or school. This activity also has educational benefits, where children learn about the life cycle of plants and the importance of plants for the environment. By planting and caring for their plants, children will experience the satisfaction of their work and gain a better understanding of ecosystems. Eco Play not only hones creativity but also shapes children's character to be more environmentally conscious and encourages them to become agents of change in the future.